Between Tradition and Digitalisation: Negotiated Mediation in Early Childhood Parenting Among Kiai Families in Sumenep Indonesia - Aziz, Thorik; Mahmud Arif; Nurjannah, Nurjannah (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study investigates how Kiai families in Sumenep, Madura, mediate digital technology in early childhood parenting through value-based filtering grounded in Islamic traditions.Design/methods/approach – An ethnographic study with phenomenological sensitivity was conducted over four months. Data were collected through participatory observation of five kiai families and in-depth interviews with ten key informants (five kiai and five nyai). Thematic analysis was employed, involving open coding, axial coding, and interpretive synthesis to identify patterns of technology negotiation.Findings – Kiai families predominantly refused children's ownership of personal digital devices, prioritising direct parent-child interaction and physical play. Technology access was filtered through religious considerations, with children exposed only to pre-selected Islamic content under strict parental supervision. However, enforcement remained inconsistent due to practical constraints, and indirect exposure through extended family networks produced observable behavioural changes, including adoption of digital expressions, reduced participation in religious routines, and shifts from active to passive play. Nyai reported greater stress in managing boundary violations, revealing gendered dimensions of mediation labour. Interpretations of problematic change were contested across kiai, nyai, and non-kiai informants.Research implications/limitations – This study demonstrates that resistance to digital parenting reflects value-based negotiation rather than technological illiteracy, challenging dominant digital parenting frameworks widely used in scholarship worldwide. By introducing negotiated mediation, the study extends parental mediation theory by foregrounding religious authority and culturally embedded conceptions of childhood as analytically significant. Limitations include the small sample size, cultural specificity of the pesantren context in Sumenep, the four-month observation period, and potential researcher bias. Findings may not be directly transferable to other religious or non-religious settings.Practical implications – Community-based digital parenting programmes should integrate religious perspectives and involve local religious leaders to increase acceptance. Educational interventions must balance digital literacy with the preservation of community values rather than imposing universal models. Originality/value – This study introduces negotiated mediation as an analytical framework explaining how religious authority shapes parental responses to digitalisation through dialectical processes between Islamic values and technological realities. It addresses a gap in the digital parenting literature by foregrounding perspectives from a religiously conservative community, thereby challenging urban-centric and secular assumptions in existing research.Paper type Research paper